(3eYQaI CUhd Yde GdMOjKs - (3eMeO Hf YHO Gddg Hf WGgQ GdfjSGHhQjs
(3ChdgG (B:s
(3GdMeO ddg Pi Gdef hGdEMSGf hdGbOQI hGdSdWGf GdPi CfTC GdNdb HQHhHjJg , hLfSge HeTjFJg s
(3BNQgG (B:s
(3BNQg eHJhQ , hBNQ GdehLhO efg HYfhGf (B" (3PcQ GdfhY GdKGfi hGdNeSjf ef eYQaI Ydhe GdMOjK (B" (3bhdg abGd LeGYI ef CFeI GdMOjK Gfg SeGY efge Cgd GdeOjfI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B2s
(3fSNI efbhdI Yf fSNI cJHgG dfaSg WGgQ Hf jMji Hf CHj GdNjQ GdYeQGfi SfI (B563 _ 564s
(3cJHJ YfhGfGJgG HGdMeQIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI LGeY GdQhVI HVhGMi UfYGA s
Keywords: (3GdMOjK h GdeUWdMs